X-ray spectroscopic studies of hot, dense iron plasma formed by subpicosecond high intensity KrF laser irradiation - Nazir, K; Rose, S; Djaoui, A; Tallents, G; Holden, MG; Norreys, P; Fews, P; Zhang, J; Failles, F (1996)
The time-integrated x-ray emission from a hot, dense iron plasma has been recorded. The iron plasma was created when a target with a 1000-Å-thick iron layer buried beneath 1000 Å of plastic was irradiated by a 300 fs pulse of 249 nm laser light at an intensity of approximately 1017 W cm-2. Two models have been used to construct a synthetic x-ray spectrum. The first employs detailed, spectroscopically accurate atomic data and the second uses a local thermodynamic equilibrium opacity model. The detailed model shows fairly good agreement with experiment whereas the opacity model only shows agreement in the gross features. © 1996 American Institute of Physics.